2018
DOI: 10.1007/s13205-017-1080-3
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting and genetic purity assessment of F1 barley hybrids and their salt-tolerant parental lines using nSSR molecular markers

Abstract: Hybridity and the genuineness of hybrids are prominent characteristics for quality control of seeds and thereby for varietal improvement. In the current study, the cross between two local barley genotypes (Ardhaoui: female; Testour: male) previously identified as susceptible/tolerant to salt stress in Tunisia was achieved. The hybrid genetic purity of the generated F putative hybrids and the fingerprinting of the parents along with their offspring were assessed using a set of 17 nuclear SSR markers. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…In our present study, the similar banding patterns (Fig. 3) as Ben Romdhane et al (2018) were observed in the true hybrids, which are co-dominant SSR markers from both parents. However, the banding patterns of the false hybrids were only displayed in either female parent (P 1 ) (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our present study, the similar banding patterns (Fig. 3) as Ben Romdhane et al (2018) were observed in the true hybrids, which are co-dominant SSR markers from both parents. However, the banding patterns of the false hybrids were only displayed in either female parent (P 1 ) (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The former, which is relied on the different phenotypic traits of hybrids and their parental lines, is considerably restricted for the limited intuitive agronomical traits, or because some agronomical traits can be detected only in the particular plant growth period, and some traits are very vulnerable to the environmental conditions. The assessment of genetic purity of hybrids via molecular fingerprinting or banding patterns of their parental lines based on SSR markers have been utilized in some crops, such as in maize (Hipi et al, 2013), rice (Bora et al, 2016), and barley (Ben Romdhane et al, 2018). In our present study, the similar banding patterns (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former, which is relied on the different phenotypic traits of hybrids and their parental lines, is considerably restricted for the limited intuitive agronomical traits, or because some agronomical traits can be detected only in the particular plant growth period, and some traits are very vulnerable to the environmental conditions. The assessment of genetic purity of hybrids via molecular fingerprinting or banding patterns of their parental lines based on SSR markers have been utilized in some crops, such as in maize (Hipi et al, 2013), rice (Bora et al 2016), and barley (Ben Romdhane et al, 2018). In our present study, the similar banding patterns (Figure 3) as Ben Romdhane et al (2018) were observed in the true hybrids, which are co-dominant SSR markers from both parents.…”
Section: Discussionsupporting
confidence: 83%
“…2 plant). The false hybrids may be due to unsuccessful hybridization, impure male parent and/or under an incompletely isolated pollination resulting in no parental pollen infiltration, and so on (Ben Romdhane et al, 2018).Thus, 30 true hybrids (accounting for 14.1%) were successfully obtained from the harvested 213 single hybrid plants of the designed 11 cross combinations, but a large difference of the proportion of true hybrid was PeerJ reviewing PDF | (2018:09:31658:1:2:NEW 20 Dec 2018)…”
Section: Discussionmentioning
confidence: 99%